DISKURSUS SESAT DALAM MEDIA MUSLIM ONLINE - Imamah (Al'Adalah, 2015)
In the islamic world, the information technology, not only has led of the way fellow muslim communicate, but also how they receive local culture and the culture the world differently. Of course, it bearing the good and bad, because indirectly the internet has reduce the world “real” be the “virtual” world or known by cyberspace. There are many the website based ideology religion, who most of them supply the knowledge and experience religious, even in a particular approach until at the level of propoganda ideology militants and anti-deviate movement. One site online media of islam is nahimunkar.com who puts islam as “victims” from the threat the existence of the deviate group. Space the interaction that recognized is only a narrative about “war field”, no tolerance for know each other and interact should relations humanity, but from the beginning the existence of deviate group described naturally as “evil”. Social reality created nahimunkar.com about “deviate group” formed in a manner framing with exaggerate a fact to excess. The dissemination of information, news, knowledge carried out consistently is also able to to “control” the community to being in “fear” space through interaction and meanings produced by media.